Ablative Fractional 10 600 nm Carbon Dioxide Laser Versus Non-ablative Fractional 1540 nm Erbium-Glass Laser in Egyptian Post-acne Scar patients - Elsaie, Mohamed; M. Ibrahim, Shady; Saudi, Wael (Journal of Lasers in Medical Sciences, 2017)
Introduction: Non-ablative fractional erbium-doped glass 1540 nm and fractional ablative 10600 nm carbon dioxide lasers are regarded as effective modalities for treating acne atrophic scars. In this study, we aimed to compare the effectiveness of fractional CO2 laser and fractional non-ablative 1540 nm erbium doped glass laser in treating post acne atrophic scars in Egyptian patients. Methods: Fifty-eight patients complaining of moderate and severe acne atrophic scars were randomly divided into 2 groups of 29 patients each. Both groups were subjected to 4 treatment sessions with 3 weeks interval and were followed up for 3 months. In group A, enrolled patients received CO2 laser, while in group B, patients were treated with 1540 nm erbium glass fractional laser. Results: Clinical assessment revealed that the mean grades of progress and improvement were higher with fractional 10600 nm CO2 laser but with non-significant difference between both treatments (P = 0.1). The overall patients’ satisfaction with both lasers were not significantly different (P = 0.44). Conclusion: Both fractional ablative CO2 and fractional non-ablative erbium glass lasers are good modalities for treating acne scars with a high efficacy and safety profile and good patient satisfaction. The fractional ablative laser showed higher efficacy while non-ablative laser offered less pain and shorter downtime.